Evolution of wave fields in block relaxing media - Danylenko, V. A.; Danevych, T. B.; Skurativskyi, S. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
A continual model for block media is studied. It takes the discontinuities of velocities and stresses between structural elements of media into account. Using the methods of the reductive theory of perturbations, the (1 + 2) second order amplitude equation of the Burgers type is constructed. Kink- like wave and self-similar solutions of the amplitude equation are derived.